Pengaruh Indeks Ketahanan Pangan, Pengeluaran Pemerintah di Bidang Pendidikan dan Kesehatan Terhadap Indeks Pembangunan Manusia pada 10 provinsi di Pulau Sumatera - Litta Rizki Ardiningrum; Junaidi Junaidi; Etik Umiyati (e-Jurnal Ekonomi Sumberdaya dan Lingkungan, 2021)
This study aims to: 1) analyze trends in the HDI, Food Security Index, Government Spending in Education and Health between Provinces on the island of Sumatra. 2) analyze the influence of the Food Security Index, Government Expenditure in Education and Health on the Human Development Index on the island of Sumatra. This study uses secondary data available from the Food Security Agency and the Central Statistics Agency in 2014-2018. The method used is descriptive and quantitative methods using panel data analysis tools. This study found that: 1) the development of HDI in 10 Provinces of Sumatra increased each year but tended to be slow, the development of government spending in education and health in 10 Provinces of Sumatra fluctuated each year but was still in the minimum provisions of the regional budget, and the Index Food Security in 10 Provinces in Sumatra also experienced fluctuating developments. 2) the variable Food Security, Government Spending in the field of Education and Health partially and simultaneously has a significant positive effect on the Food Security Index.